Impact of Social Media on Consumer Behaviour - et. al., Amandeep Singh, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper encompasses the research studies done on the impact of social media on consumer behaviour. Social media is used by billions of people around the world and has fast become one of the defining technologies of our time. People are using various social media websites and because of that the entire marketing landscape is changing. Massive audience is available who are spending many hours a day using social media across the various platforms and are majorly involved in information processing, entertainment and social connection activities, it is not surprising that marketers have started utilising social media as a marketing channel. Companies now place considerable value on the way in which social media can be used to shape consumer’s brand/product perception and influence their buying decision. Rather than focusing on short-term advertising through technology, companies are integrating social media mechanisms to enhance the relationship with consumers. Therefore, companies need to better understand the changing behaviour of consumers, in order to create mutual benefits from the use of social media. So, the research paper talks about what activities the consumer are involved in, how branding on social media is important and how it can help in marketing the goods/services. It also highlights how user generated content helps in marketing of a company and what will be the future of social media and areas the companies should focus on which will impact the consumers behaviour.